ANALISIS PENERAPAN METODE UMMI DALAM PEMBELAJARAN AL-QUR’AN DI KELAS II MAHONI SD ISLAM AQZIA TELUK KUANTAN - Mardianto Mardianto; Bustanur Bustanur; Zulhaini Zulhaini (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2021)
This research is motivated by the problems found in the author's initial observations at SD Islam Aqzia Teluk Kuantan, the following symptoms were found: 1. The teacher has implemented the Ummi Method well, but the results of learning Al-Quran students are still unsatisfactory. In learning Al-Quran, there are still some students who are not satisfactory in learning Al-Quran. Of the 60 children studying in grade 1, there are (30%) children who are still slow in learning the Qur'an. 2. In learning Al-Qur'an, there are different volumes of children who learn Al-Quran. 3. There are still students who are slow to memorize the Al-Qur'an from 60 children 10-15 children have not finished memorizing from the learning targets. This study aims to determine the application of the Ummi Method in Al-Qur'an learning in Class II Mahogany Islamic Elementary School Aqzia Teluk Kuantan. Collecting data by means of observation, interviews, and documentation. And using data analysis of miles and huberman. The sample of this research consisted of 20 students, then the data were analyzed by providing an explanation of the application of the Ummi Method in Al-Qur'an Learning in Class II Mahogany SD Islam Aqzia Teluk Kuantan. Based on the results of interviews and field observations that show the application of the ummi method in learning the Al-Qur'an, the results are from the seven existing stages, which are applied four stages, then the application of learning the Al-Qur'an, the ummi method is not carried out as a whole, the results are not good.